Education And Training On Digital Classroom Design Development For Elementary School Teachers In Burneh District - Tri Wahyudi Ramdhan; Bustomi Arisandi; Muhammad Tohir; Mufaizin Mufaizin; Bahrul Ulum (Natural: Jurnal Pelaksanaan Pengabdian Bergerak bersama Masyarakat., 2024)
With the open access to information in the era of the Industrial Revolution 4.0 and the rapid development of technology, teachers are no longer the main source of learning. This requires teachers to use technology in the learning process. With the presence of gadgets that they carry everyday, they can be utilised for learning activities. The purpose of this activity is to improve teacher competence in developing digital classroom design using the google classroom application. The methods used were lectures, questions and answers, discussions, group practices, guidance services, simulations and group presentations. The results obtained show that the fourth grade teachers of elementary school in Burneh District as training participants have skills in developing digital classroom design using google classroom applications from the beginning of the learning process to learning evaluation